2016
DOI: 10.1167/16.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Disparity vergence responses before versus after repetitive vergence therapy in binocularly normal controls

Abstract: This study sought to determine whether significant changes would be observed between vergence eye movements before and after 12 hr of repetitive vergence therapy (1 hr per day on different days) in subjects with normal binocular vision compared to controls. Disparity vergence responses from 23 subjects were studied. An assessment protocol that minimized the influence of the near dissociated phoria on the disparity vergence system was designed. The following parameters were quantified for the responses: latency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 76 publications
2
23
0
Order By: Relevance
“…When the FIC is optimized meaning the eyes are brought close to the intended visual stimulus, then less modification is required from the FSC, which may be a factor leading to the sustained reduction of visual symptoms. Our laboratory has published other investigations showing optimization of the FIC in binocular normal controls after vergence therapy 21 and in those with CI. 58 A randomized clinical trial is needed to further confirm whether it is the FIC of vergence that is being optimized by OBVT in patients with CI and concussion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the FIC is optimized meaning the eyes are brought close to the intended visual stimulus, then less modification is required from the FSC, which may be a factor leading to the sustained reduction of visual symptoms. Our laboratory has published other investigations showing optimization of the FIC in binocular normal controls after vergence therapy 21 and in those with CI. 58 A randomized clinical trial is needed to further confirm whether it is the FIC of vergence that is being optimized by OBVT in patients with CI and concussion.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research shows a binocularly normal control fuses typically well within 2 seconds, typically within the first half of the first second. 21 Hence, for this study, we approximately doubled the amount of stimulus presentation time for CI patients to allow adequate time for them to fuse the symmetrical binocular vergence stimuli. The variability in duration of the presentation was designed to try to prevent anticipatory responses that are known to affect vergence responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an improvement of vergence capacities as measured by the orthoptist with a prism bar reflects what the subjects do in everyday life, converge or diverge their eyes and adjust the appropriate vergence angle better. Talasan and al. (2016) showed that orthoptic re-education leads to improvements of vergence eye movements measured with video oculography.…”
Section: Postural Control After Orthoptic Re-educationmentioning
confidence: 99%
“…There are experimental studies showing the physiological effects of specific exercises of vision therapy 5 and it has been shown even how the cortical activity is increased after the performance of repetitive vergence training. 6 Therefore, it can be said that vision therapy is science-based procedure. As in any other area of visual sciences, more research is needed to improve the procedures, to find new indications and to strengthen the reputation of this optometric field.…”
mentioning
confidence: 99%